The establishment of the Tabung Siswa (Fund for Students) to replace the system of government gratis scholarship - Ungku Abdul Aziz, Ungku Abdul Hamid
Rukun Negara and Second Malaysia Plan, the New Economic Policy were set up to create a just society, to restructure the society and to eliminate poverty so that the nation could enjoy the national wealth equally. There were some radical changes implemented in the universities admission in conjunction with these national missions. There is an increasing number of the rural area students in the universities. The scholarship is given to the rural students sometimes could barely support their tuition fees and reasonable needs. Due to the scholar group also included well-being students who do not need any financial aid and some who do not appreciate the value of scholarship, Ungku suggested that the present scholarship system should be replaced by loan system. This would gradually reduce the use of public funds and the Government could use these funds for other development. The Tabung Siswa (Fund for Students) should be established to manage all the student loans. The fund would be financed from the present Government expenditures on scholarship which would eventually cease. The loan system would provide adequate loans to the student as per their need. It would be repayable in easy installments after graduation over an eight-year period. An interest of four percent would be charged after two years of convocation. After twelve years, this Student Fund should become financially independent or self-supporting. It is suggested that this new organization would overcome the present difficulties in finding a guarantor for the scholarship agreement. In the new proposed system, the guarantor can be one of the parents of the student, who is above 18 years old. The loan would either be deducted from the salary or EPF once the student graduates and starts working. The Student Fund could offer other benefits such as education insurance to parents of potential students. The complication of Government sponsored applicants could be overcome by establishing Organisasi Kemasukan (O.K). This new organization will work closely with all the government bodies and Student Funds, and the universities admission department to allocate the agreed number of applicants for admission to all faculties in all universities. Ungku also suggested a new system of cash prizes should be created to encourage sports, cultural activities and public services. This would create a pool of graduates with a healthy body and mind, with decent behavior and characteristics of being all-rounders in sports, cultural and rural services. Besides the present system of prizes awarded to undergraduate achieving top results in examinations, cash prizes could be awarded to undergraduates showing the best rate of progress in their respective faculties. This would strengthen the academic ambition, especially of rural students. This proposal is written based on the mission of forming a just society so that all the nations could enjoy the national wealth equally. This is also to encourage more youths from the rural areas to further their studies and thus improve their financial condition and escape from the exploitation of MM system. If the Government approved the proposal, a study should be carried out to examine and define the details about the Student Fund system.